Rio - 10 Years After: A Critical Appraisal of Climate Policy - Christoph Böhringer; Carsten Vogt (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2002)
Ten years after the initial Climate Change Convention from Rio in 1992, the developed world is likely to ratify the Kyoto Protocol which has been celebrated as a milestone in climate protection. Standard economic theory, however, casts doubt that Kyoto will go beyond symbolic policy. In this paper we show that the final concretion of the Kyoto Protocol obeys the theoretical prediction: Kyoto more or less boils down to business-as-usual without significant compliance costs to ratifying parties.
Keywords: D58; Q43; Q58; 330; climate policy; emission trading; hot air; Klimaschutz; Umweltabkommen; Wirtschaftspolitische Wirkungsanalyse; Kritik; Welt